PEMBENTUKAN CREATIVE LEADERSHIP DAN INNOVATION WORK BEHAVIOR MELALUI PERAN ORGANIZATIONAL CULTURE DALAM KONTEKS START-UP DI JAKARTA - Nugroho, Robertus Adi; Rosyadi, Jessica Angelia (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This study addresses the critical challenge of fostering innovative work behavior in start-ups, where agility and adaptability are essential to thriving in dynamic markets. Existing literature suggests that while organizational culture can influence employee innovation, the role of creative leadership as a mediator remains underexplored, particularly within start-ups. This research examines how an innovation-supportive organizational culture influences creative leadership and innovative work behavior, focusing on Jakarta-based start-ups. A quantitative research approach was employed, using structured questionnaires from 219 individuals, and the statistical analysis of Partial-Least-Squares Structural-Equation Modeling (PLS-SEM). Findings reveal that a supportive organizational culture significantly enhances both creative leadership and innovative work behavior, while creative leadership partially mediates the relationship, translating cultural values into innovation. Despite limitations, including the focus on Jakarta and reliance on self-reported data, these findings lay a foundation for future research on innovation within start-ups.